Business and entrepreneurship is declining as scholarly field: Empirical evidence. - Wim Naudé (PLoS ONE)
This paper presents evidence from 68,792 papers published between 1961 and 2020 that progress in the scholarly field of business and entrepreneurship is declining. It is found that the annual number of papers published in the field has increased exponentially since the Second World War, growing on average by 17% annually since 1961; the average disruption score of papers have declined by a factor of 36 between the 1960s and the 2010s; and that the average team size per paper has increased from 1,6 between 1960-1980-2,4 between 2000 and 2020. Estimates from an ideas production function suggest that the field is getting fished out and that researchers may be stepping on one another's toes. A Wald-test indicates that a structural break in the disruptiveness of business and entrepreneurship and papers occurred around 1999. These results could reflect pathologies in how research in the field is organized and/or that the field has matured.